Factors Associated with Mortality in Severe Acute Cholangitis in a Moroccan Intensive Care Unit: A Retrospective Analysis of 140 Cases - Soumaya Touzani; Abderrahim El Bouazzaoui; Fatima Bouyarmane; Kaoutar Faraj; Nawfal Houari; Brahim Boukatta; Nabil Kanjaa (Gastroenterology Research and Practice)
Background. Severe acute cholangitis is a life-threatening biliary infection, leading to organ dysfunction, septic shock, and naturally death. Mortality has dropped significantly in the past years through improving resuscitation and biliary drainage techniques. The aim of our study is to analyze our daily practice and the factors associated with mortality. Methods. A retrospective study including severe acute cholangitis patients admitted to our unit from January 2009 to December 2018. Variables analyzed (univariate then multivariate analysis) were age, sex, history, origin, evolution time, bilirubin, etiology, organ dysfunction, qSOFA, SOFA, TOKYO, biliary drainage timing and technique, shock, antibiotherapy, and resuscitation. Results. 140 patients were included in this study. Average age was 61. Sex ratio M/F was 0.59. Lithiasis etiology was dominant (69%). SOFA average score upon admission was 8. Ceftriaxone + metronidazole was the empirical antibiotic used in 87%. Average time to biliary drainage was 1.58±0.89 days. Endoscopic unblocking was the technique used in 76%. Mean duration of ICU stay was 6 days. Mortality rate was 28%. Statistically significant factors for mortality (p<0.05) were history of taking anticoagulant treatment, use of catecholamines and mechanical ventilation during ICU stay, and delay in consultation and administration of antibiotic therapy. Conclusions. Early recognition, antibiotics, resuscitation, and minimally invasive biliary drainage have improved patient outcomes although there is still progress to be made. Moreover, as multiple organ failure is often associated with mortality in severe acute cholangitis, predictive risk factors of organ failure should be more investigated.